Land Acquisition Conflicts in the Construction of the Jombang-Mojokerto Toll Road - Muhammad Daffa Syahputra; Frederick Xaverius Tjipto; Albert Lodewyk Siahaan (Transpublika Publisher, 2025)
The development of toll road infrastructure is one of the government's strategic steps in improving connectivity and national economic growth. However, the land acquisition process, which is a prerequisite for development, often leads to conflicts between the government and landowners. This paper discusses agrarian conflicts that occurred in the Jombang-Mojokerto Toll Road construction project, by highlighting the main causes of disputes, namely the discrepancy in the value of compensation and the lack of transparency in the deliberation process. Based on agrarian law studies and analysed case studies, this paper proposes several conflict resolution solutions, including open deliberations, fair compensation, strong legal protection, and socio-economic assistance for affected residents. The findings of this study demonstrate that the success of infrastructure projects is dependent not just on technical considerations, but also on the importance of a fair and inclusive land acquisition process. Discrepancies in compensation values can cause social resistance, impeding projects and undermining community trust in government policy. The study also emphasises the significance of providing communities with a better legal awareness of their rights and land acquisition methods in order to avoid misinformation to their disadvantage. This study is unique in that it focuses on social disputes caused by variations in compensation values in toll road projects, as well as how participatory land acquisition techniques can affect project success. This study provides new insights into the relevance of including social issues in land.